WORD FORMATION THROUGH COMPOUNDING IN GEN-Z SLANG ON TIKTOK - DJOHAN, MEIDINA SINRANG SJAMSU; WAGATI, WAGATI; KADIR, PUSPA MIRANI (Universitas Negeri Medan, 2024)
Language is dynamic and reflective of societal changes, with Gen-Z, the first true digital natives, playing a pivotal role in linguistic evolution. This study examines the phenomenon of word formation through compounding in Gen-Z slang on TikTok, exploring its linguistic structures and meanings. By analyzing the common compounding patterns in Gen-Z slang, we gain insights into the creative processes and social influences shaping language use among this demographic. Utilizing a qualitative approach, data was collected from TikTok videos and comments between January 2023 and May 2024. The findings reveal 15 distinct compound words, with compound nouns being the most prevalent, followed by compound verbs and compound adjectives. Endocentric compounds were more common than exocentric ones. This research highlights the innovative nature of language within Generation Z, reflecting their values of self-expression, technological engagement, and creative problem-solving. The study underscores the role of social media in shaping contemporary language and provides a foundation for further exploration of linguistic innovations and their implications for language development and cultural expression in the digital age.